Synergy of a genetic algorithm and simulated annealing to maximize real power loss reductions in transmission networks - El-Fergany, Attia A.; Othman, Ahmed M.; El-Arini, Mahdi M. (International journal of electrical power & energy systems, 2014)
•Hybrid approaches of GA and hybridized SA with PS to minimize power loss proposed.•Significant loss reductions have been realized with different operating scenarios.•Single line outage and overloading patterns have been examined and analyzed.•Total fuel costs and amount of emissions have been observed and reported.•Effects of changing the control variables have been investigated and highlighted. This manuscript applies a hybrid integrated heuristic approaches to minimize real power losses in the given power system network. Synergy of a genetic algorithm and hybridized simulated annealing with pattern search are proposed to decide the optimum adjustments to the continuous and the discrete control variables. The proposed method has been applied to several transmission networks with different operating scenarios to investigate its effectiveness and applicability. The numerical results and simulations with different load patterns and single line outages have been demonstrated and evaluated. The results achieved show the effectiveness and robustness of the proposed hybrid approach compared to other heuristic methods.